Pengaruh Penggunaan Ekstrak Serai (Cymbopogon Citratus) Pada Sanitasi Telur Puyuh Terhadap Daya Tetas Telur Puyuh - Halim Anas Abyan; Filiandiva Praginta Putri; Yuke Dwi Yanti (Jurnal Ilmu Peternakan Indonesia, 2026)
Hatching egg shells are prone to microbial contamination, which can reduce hatchability, creating a need for natural sanitizing agents as alternatives to chemical disinfectants. This study aimed to examine the effect of lemongrass extract (Cymbopogon citratus) sanitation on quail eggshells toward hatchability. The research was conducted in June 2026 at the Hatchery Laboratory of IPB University Vocational School, Sukabumi Campus, using 82 Japanese quail eggs divided into two treatments: P0 (no shell sanitation) and P1 (shell sanitation using lemongrass extract), with 41 eggs per treatment. Hatchability data were tested for normality using Shapiro-Wilk, and since the data were not normally distributed, analysis proceeded using the Mann-Whitney test at a 5% significance level. Results showed a highly significant difference between the two treatments (Asymp. Sig. 2-tailed = 0.007; p<0.05). The average hatchability of P1 reached 78.00±0.54%, higher than P0 at only 59.57±0.54%, representing an 18.43% increase. This improvement is attributed to the citral, geranial, neral, flavonoid, saponin, and tannin content of lemongrass extract, which exhibit antibacterial activity against both gram-positive and gram-negative bacteria, thereby reducing microbial contamination on the shell without impairing pore function for gas exchange. It can be concluded that lemongrass extract sanitation significantly improves quail egg hatchability and has potential as an alternative natural sanitizing agent to replace chemical disinfectants.